1974
DOI: 10.1021/jo00926a003
|View full text |Cite
|
Sign up to set email alerts
|

1-Methyl-3-phospholanol system. Synthesis and stereochemistry

Abstract: l-Methyl-3-phospholanol (cis, trans) has been prepared by reduction of 1 -methyl-3-phospholanone with several agents, preferably lithium aluminum hydride, as well as by P-deoxygenation of the alcohol mixture formed on catalytic hydrogenation of l-methyl-3-phospholanone 1-oxide. The phospholanol mixture is easily analyzed by the well-separated (13 Hz) PCH3 nmr signals; the downfield signal is attributed to the cis isomer, which predominated (84%) from the various reductions of the phospholanone. The route via t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0
1

Year Published

1974
1974
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…In previous work with the phospholene system, we have shown that a halogen atom separated by a double bond from a phosphoryl2 (1) or thiophosphoryl3 (2) group is activated…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In previous work with the phospholene system, we have shown that a halogen atom separated by a double bond from a phosphoryl2 (1) or thiophosphoryl3 (2) group is activated…”
mentioning
confidence: 99%
“…Synthesis and Structure of 3-Amino-2-phospholene Sulfides. The enamines 7-10 were prepared in 72-82% yield by refluxing a mixture of the amine and 1 -methyl-3-chloro-2-phospholene sulfide (2). The products were nonhygroscopic solids, easily recrystallized from common solvents.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, aminophospholene oxides were prepared by multi-step syntheses. 10,11 ‡ (1S*,2R*,6R*,8R*)-5-Benzyl-9,9-dimethyl-5-oxo-4-phenyl-5-phosphatricyclo[6.1.1.0 2,6 ]dec-3-en-3-ylamine 3: white crystals, mp 218-220 °C (CCl 4 -MeCN, 5:1 v/v), [a] 25 0.0. 1 H NMR (500 MHz, CDCl 3 ) d: 0.84 (s, H 11 ), 1.17 (s, H 12 ), 1.43 (d, H 10β , J 9.7 Hz), 1.76 (ddddd, H 7β , J 13.7, 13.2, 11.7, 1.4 and 1.4 Hz), 1.88 (dddd, H 8 , J 5.7, 5.7, 3.9 and 2.1 Hz), 2.00 (m, H 1 ), 2.02 (m, H 10α ), 2.19 (dddd, H 6 , J 10.5, 9.7, 9.4 and 2.8 Hz), 2.41 (dddd, H 7α , J 20.6, 13.7, 3.8 and 2.8 Hz), 2.88 (dddd, H 2 , J 16.3, 9.0, 1.0 and 1.0 Hz), 3.12 (d, CH 2 Ph, J 16.4 Hz), 4.46 (s, NH 2 ), 7.00 (m, H b' ), 7.09-7.22 (m, H c' , H d' and H d ), 7.35 (t, H c , J 7.5 Hz), 7.52 (d, H b , J 7.5 Hz).…”
mentioning
confidence: 99%
“…Unter Berücksichtigung der bisherigen Erfahrungswerte kann dann auch das CH3-Signal bei tieferem Feld den ci-s-ständigen Methylgruppen zugeordnet werden [10].…”
unclassified